2011
DOI: 10.1590/s1807-59322011000400016
|View full text |Cite
|
Sign up to set email alerts
|

E-learning program for medical students in dermatology

Abstract: INTRODUCTION:Dermatological disorders are common in medical practice. In medical school, however, the time devoted to teaching dermatology is usually very limited. Therefore, online educational systems have increasingly been used in medical education settings to enhance exposure to dermatology.OBJECTIVE:The present study was designed to develop an e-learning program for medical students in dermatology and evaluate the impact of this program on learning.METHODS:This prospective study included second year medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 23 publications
3
42
0
11
Order By: Relevance
“…They attribute it to students spending an additional 20 hours on the multimedia resources in the semester. Similar advantage with blended learning was noted by Silva et al & Pereira et al in their studies conducted in the departments of dermatology and anatomy [17,18]. Contrary to the above cited studies, e-learning did not improve the test scores in this study.…”
Section: Total Scoressupporting
confidence: 84%
“…They attribute it to students spending an additional 20 hours on the multimedia resources in the semester. Similar advantage with blended learning was noted by Silva et al & Pereira et al in their studies conducted in the departments of dermatology and anatomy [17,18]. Contrary to the above cited studies, e-learning did not improve the test scores in this study.…”
Section: Total Scoressupporting
confidence: 84%
“…In this respect, digital resources are becoming an important part of health education (Schultze-Mosgau et al, 2004;Beux & Fieschi, 2007;Chen et al, 2008;Turmezei, 2009;Silva et al, 2011). It is therefore expected that the inclusion of these resources in the study of morphological sciences will facilitate access to practical contents involved in distance learning in order to extend the benefits to different education sectors of the society.…”
Section: Discussionmentioning
confidence: 99%
“…Upon examining additional research, it was revealed that blended learning method has been implemented in subjects such as dentistry (Bains, Reynolds, McDonald, & Sherriff, 2011;Yang, Zhang, & Bridges, 2012), dermatology (Silva, Souza, Filho, Medeiros, & Criado, 2011), cardiovascular system Figure 11. Views of the students as a new learning approach Figure 12.…”
Section: Continuitymentioning
confidence: 99%